2023
DOI: 10.3389/fimmu.2023.1139595
|View full text |Cite|
|
Sign up to set email alerts
|

Crosstalk between cGAS-STING pathway and autophagy in cancer immunity

Abstract: The cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway is critical in cancer immunity. Autophagy is a highly conserved process that is responsible for the degradation of cytoplasmic material and is involved in both innate and adaptive immunity. Recently, cGAS-STING and autophagy have been shown to be interconnected, which may influence the progression of cancer. Although cGAS-STING and autophagy have been shown to be interrelated in innate immunity, little has been reported about cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 171 publications
0
12
0
Order By: Relevance
“…But which signals are critical for conveying the proinflammatory and antitumor effects of autophagy ablation in TECs? Recent studies have largely focused on the crosstalk between autophagy and STING pathways and their effects on cancer cell immunogenicity/antitumor immunity in response to therapy (Zhao et al , 2022; Lu et al , 2023). However, emerging evidence indicates that the homeostatic and pathological functions of autophagy in ECs are shaped by the cellular and tissue/microenvironment context (Reglero‐Real et al , 2021; Amersfoort et al , 2022; Meçe et al , 2022) and respond to different inflammatory cues.…”
Section: Discussionmentioning
confidence: 99%
“…But which signals are critical for conveying the proinflammatory and antitumor effects of autophagy ablation in TECs? Recent studies have largely focused on the crosstalk between autophagy and STING pathways and their effects on cancer cell immunogenicity/antitumor immunity in response to therapy (Zhao et al , 2022; Lu et al , 2023). However, emerging evidence indicates that the homeostatic and pathological functions of autophagy in ECs are shaped by the cellular and tissue/microenvironment context (Reglero‐Real et al , 2021; Amersfoort et al , 2022; Meçe et al , 2022) and respond to different inflammatory cues.…”
Section: Discussionmentioning
confidence: 99%
“…From the observation that tumor cells are capable of modulating autophagy to promote their survival and resistance to current clinical treatments (radiotherapy and chemotherapy), studies about autophagy in cancer have expanded dramatically [ 197 , 198 ]. On the basis of these studies, few novel autophagy inhibitors have been identified which have been then tested in human clinical trials.…”
Section: Potential Clinical Application For Adoptive Cell-therapymentioning
confidence: 99%
“…Psoriasis is an autoinflammatory disease that affects not only skin but multiple organs thus being associated with many comorbidities (1). The prevalence of psoriasis differs between the regions, i.e.…”
Section: Introductionmentioning
confidence: 99%